Studies on Growth and Various Properties of Triglycine Sulfate (TGS) Crystals Doped with Copper Sulphate - P. Selvarajan, K. Balasubramanian (Recent Research in Science and Technology, 2010)
Pure and copper sulpahte-doped Triglycine Sulfate(TGS) salts were synthesized and single crystalsÃ‚Â of the synthesized salts were grown from aqueous solutions by slow evaporation technique.Ã‚Â TheÃ‚Â structural studies on the grown crystals were carried out byÃ‚Â single crystal XRD analysis and found that the grown crystals crystallize in monoclinic structure. The FTIR spectra have been recorded in the range 500-4000 cm-1 Ã‚Â andÃ‚Â Ã‚Â the functional groupsÃ‚Â of the grown crystals have been identified.Ã‚Â UV-VisibleÃ‚Â Ã‚Â spectra show that the grown crystals have wide optical transparency in the entire visible region. Atomic absorption study reveals the presence of copperÃ‚Â inÃ‚Â the doped TGS crystals.Ã‚Â Ã‚Â Density of the samples have been measured by floatation method. The dielectricÃ‚Â studiesÃ‚Â for the pure and copper sulphate-doped TGS crystalsÃ‚Â have been performed by measuring the dielectric parameters like dielectric constantÃ‚Â and dielectric lossÃ‚Â at a constant frequency of 1000 HzÃ‚Â with theÃ‚Â temperatures ranging from 30Ã‚Â toÃ‚Â 75 oCÃ‚Â and this study reveals an increase of dielectric constant and loss when TGS crystalÃ‚Â is doped with copper sulphate.Ã‚Â MicrohardnessÃ‚Â studies have been carried outÃ‚Â to analyseÃ‚Â the mechanical strength of the samples.Ã‚Â